Inovasi Keuangan Sosial Islam Untuk Ketahanan Ekonomi Di Provinsi Bengkulu - Putri, Fiona Hasdo; Alqdri , M. Wahyu (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
This research explores the role of Islamic social finance innovations in strengthening economic resilience in Bengkulu. Utilizing data from the National Socioeconomic Survey (SUSENAS), the study highlights the potential of zakat, waqf, and Islamic microfinance as tools for sustainable economic development. Key findings reveal that despite a reduction in the poverty rate from 15.22% in 2021 to 14.62% in 2022, disparities remain across districts. Optimizing Islamic social finance is critical to bridging economic inequality and improving community welfare. Challenges include limited public awareness and institutional inefficiencies. This study concludes with recommendations for digitalization, institutional strengthening, and stakeholder collaboration to maximize the benefits of Islamic social finance innovations. The results of the study stated that Islamic social finance is a powerful tool for economic transformation, its successful implementation in Bengkulu requires a comprehensive and multi-faceted approach that includes effective management, public engagement, a strong institutional framework, and local collaboration. If these elements are adequately addressed, Islamic social finance can play a transformative role in reducing poverty, bridging economic disparities, and promoting sustainable community development in Bengkulu.